2020
DOI: 10.1002/anie.202009353
|View full text |Cite
|
Sign up to set email alerts
|

The [(NHC)B(H)C6F5]+ Cations and Their [B](H)−CO Borane Carbonyls

Abstract: Hydride abstraction from the heterocyclic carbene borane adducts (NHC)BH 2 C 6 F 5 (NHC: IMes or IMe 4) gave the BÀH containing [(NHC)B(H)C 6 F 5 ] + borenium cations. They added carbon monoxide to give the respective [(NHC)B-(H)(C 6 F 5)CO] + boron carbonyl cations. Carbon nucleophiles add to the boron carbonyl to give [B](H) acyls. Hydride reduced the [B]CO cation to hydroxymethylborane derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 69 publications
(32 reference statements)
0
18
0
Order By: Relevance
“…It was recently shown that hydride removal from the NHC N,N'-bis (2,4,6-trimethylphenyl)imidazolylidene (IMes) borane adduct 6a gave the [IMesB(H)C 6 F 5 ] + cation, [13] which upon heating underwent intramolecular CÀHactivation [14] at aCH 3 group of amesityl substituent with loss of H 2 to give the cyclization product 4a.This was now readily deprotonated at the acidified CH 2 group adjacent to the B-C 6 F 5 moiety to give the neutral product 5a (Scheme 2). Its X-ray crystal structure analysis showed the presence of aB = Cdouble bond (C17-B1: 1.456( 4) ,cf.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was recently shown that hydride removal from the NHC N,N'-bis (2,4,6-trimethylphenyl)imidazolylidene (IMes) borane adduct 6a gave the [IMesB(H)C 6 F 5 ] + cation, [13] which upon heating underwent intramolecular CÀHactivation [14] at aCH 3 group of amesityl substituent with loss of H 2 to give the cyclization product 4a.This was now readily deprotonated at the acidified CH 2 group adjacent to the B-C 6 F 5 moiety to give the neutral product 5a (Scheme 2). Its X-ray crystal structure analysis showed the presence of aB = Cdouble bond (C17-B1: 1.456( 4) ,cf.…”
Section: Resultsmentioning
confidence: 99%
“…In solution ([D 2 ]dichloromethane,2 99 K) compound 5b shows a 11 BNMR signal at 15.6 (Dd 19 F m,p = 3.7 ppm). The carbon atom of the N1-C1-N2 unit shows an iminium-type 13 CNMR feature at d 166. 5…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We had described that the cyclic boraalkene 1 was readily prepared starting from the corresponding [(IMes)(C 6 F 5 )BH] + borenium cation (with [B(C 6 F 5 ) 4 ]anion) 11 by a sequence involving thermally induced intramolecular C-H activation at an ortho-methyl group of a NHC mesityl substituent (with H 2 formation) followed by deprotonation. 12 Compound 1 was now found to rapidly react with nitrosobenzene 13 The X-ray crystal structure analysis of compound 2 showed bond lengths inside the newly formed four-membered heterocycle of 1.505( 4) Å (B1-O1), 1.624( 4) Å (B1-C17), 1.504(3) Å (N3-C17) and 1.475(3) Å (N3-O1).…”
Section: Resultsmentioning
confidence: 99%